School support for siblings of patients with cancer : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Lamb, Erika (Massey University, 2015)
This research project investigated the importance of providing support structures within school communities for siblings of patients diagnosed and treated for cancer. A cancer diagnosis is traumatic and devastating for the child or young person with cancer but what sometimes gets lost is the impact such a medical event can have on siblings whose need for a range of emotional, social, academic, and physical support tend to be overshadowed by the focus on the patient and how the parents/caregivers cope. Sibling members of CanTeen New Zealand (an organisation which supports young people living with cancer and their siblings) were invited to participate in a nation-wide online survey or a focus group session in Auckland, both exploring siblings’ perceptions of school based support. Both methods of data collection were created with the support of CanTeen staff and were informed by the literature surrounding support for siblings living in families affected by cancer. Participants responded to questions regarding who supported them at school, how they were supported, what they wanted members of the school community to understand, and what supports they wish had been available while they were on their cancer journey. Highlighted in the research findings were that different school communities fulfil different sibling needs, siblings’ everyday lives are disrupted by their brothers’ or sisters’ cancer diagnoses, every cancer journey is different (shaped by a sibling’s unique familial and community circumstances), and there is a need for home-school partnerships to ensure the best outcomes for siblings. By having siblings express their thoughts and feelings regarding the cancer journey in their own words, this research can provide valuable insight for schools who have students living in families affected by cancer and can act as a guide for how to best support the needs of this population.
Keywords: Cancer in children; Patients; Family relationships; Brothers and sisters; Psychological aspects; Educational counseling